Superior field emission properties of layered WS2-RGO nanocomposites - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Scientific Reports, 2013)
We report here the field emission studies of a layered WS2-RGO composite at the base pressure of similar to 1 x 10(-8) mbar. The turn on field required to draw a field emission current density of 1 mu A/cm(2) is found to be 3.5, 2.3 and 2 V/mu m for WS2, RGO and the WS2-RGO composite respectively. The enhanced field emission behavior observed for the WS2-RGO nanocomposite is attributed to a high field enhancement factor of 2978, which is associated with the surface protrusions of the single-to-few layer thick sheets of the nanocomposite. The highest current density of similar to 800 mu A/cm(2) is drawn at an applied field of 4.1 V/mu m from a few layers of the WS2-RGO nanocomposite. Furthermore, first-principles density functional calculations suggest that the enhanced field emission may also be due to an overalp of the electronic structures of WS2 and RGO, where graphene-like states are dumped in the region of the WS2 fundamental gap.

Enhanced field emission properties of doped graphene nanosheets with layered SnS2 - Rout, Chandra Sekhar; Joshi, Padmashree D.; Kashid, Ranjit V.; Joag, Dilip S.; More, Mahendra A.; Simbeck, Adam J.; Washington, Morris; Nayak, Saroj K.; Late, Dattatray J. (Applied Physics Letters, 2014)
We report here our experimental investigations on p-doped graphene using tin sulfide (SnS2), which shows enhanced field emission properties. The turn on field required to draw an emission current density of 1 mu A/cm(2) is significantly low (almost half the value) for the SnS2/reduced graphene oxide (RGO) nanocomposite (2.65 V/mu m) compared to pristine SnS2 (4.8 V/mu m) nanosheets. The field enhancement factor beta (similar to 3200 for the SnS2 and similar to 3700 for SnS2/RGO composite) was calculated from Fowler-Nordheim (F-N) plots, which indicates that the emission is from the nanometric geometry of the emitter. The field emission current versus time plot shows overall good emission stability for the SnS2/RGO emitter. The magnitude of work function of SnS2 and a SnS2/graphene composite has been calculated from first principles density functional theory (DFT) and is found to be 6.89 eV and 5.42 eV, respectively. The DFT calculations clearly reveal that the enhanced field emission properties of SnS2/RGO are due to a substantial lowering of the work function of SnS2 when supported by graphene, which is in response to p-type doping of graphene. (C) 2014 AIP Publishing LLC.

Photosensitive field emission study of SnS2 nanosheets (27th International Vacuum Nanoelectronics Conference ) - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (2014 27TH International Vacuum Nanoelectronics Conference (IVNC), 2014)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to Field Emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solution are used. The FE study is carried out in all metal Ultra High Vacuum (UHV) chamber in planar diode configuration at a base pressure of similar to 10(-8) torr. A maximum current density of 110 mu A/cm(2) was attainable. The turn on field required to draw a current density of 1 mu A/cm(2) is found to be 2.6 V/mu m. A separate study was carried out to investigate the photosensitivity of the emitter by illuminating the specimen under visible light. In dark, the FN plot is non-linear, indicative of semiconductor nature of the emitter. However, on illumination, the FN plot is observed to be linear. This remarkable change can be explained by the photoconductivity imparted on illumination. The field at the tip is high in presence of light, than in dark, due to enhanced conductivity. It is also observed that on switching ON the light, the FE current increases almost instantaneously. Repetitive switching is observed at a fixed applied voltage, generating current pulses. The visible light soaking of the sample is carried out by illuminating the lamp for more than 100 minutes, where the current seems to saturate. On switching off the lamp the emission current decayed almost to its initial value exponentially. The photosensitivity has been studied for different wavelengths in the visible spectra. The maximum photosensitive field emission is observed for green filter. With this photoresponse, it is envisaged that SnS2 nanosheets are a potential candidate for optoelectronic applications of field emitters.
Keywords: field emission; photosensitivity; Photoswitching

Photosensitive field emission study of SnS2 nanosheets - Joshi, Padmashree D.; Joag, Dilip S.; Rout, Chandra Shekhar; Late, Dattatray J. (Journal of Vacuum Science & Technology B, 2015)
SnS2 nanosheets (SnS(2)NSs), synthesized by one-step hydrothermal reaction, are subjected to field emission (FE) studies. For synthesis, specific concentrations of Na2SnO3 and thioamide solutions are used. The FE study is carried out in a planar diode configuration at a base pressure of similar to 10(-8) mbar. The emission photosensitivity is also investigated by illuminating the specimen with a visible light source. In dark, the turn on field, the electric field required to obtain a current density of 1 mu A/cm(2), is found to be 5.9 V/mu m. Upon illumination, the emitter with visible light, it is found to reduce to 5.0 V/mu m. A significant change in the nature of the Fowler-Nordheim plot with light illumination is also observed and has been explained on the basis of photoconductivity. Repetitive switching ON and OFF the light source, at a fixed applied voltage, is found to generate current pulses. The photosensitivity is also studied with various color filters. With the photoswitching and the enhanced field emission properties, it is envisaged that SnS(2)NSs possess a potential for optoelectronic applications of field emitters. (C) 2014 American Vacuum Society.

Nonlinear Fowler-Nordheim behavior of a single SnO2 nanowire - Joshi, Padmashree D.; Joag, Dilip S.; Late, Dattatray J.; Mulla, Imtiaz S. (Journal of Vacuum Science & Technology B, 2017)
The present work deals with the field emission study on multiple SnO2 nanowires synthesized by a simple thermal evaporation method. The randomly oriented multiple nanowires grown by the vapor-liquid-solid mechanism exhibit low turn on field (0.8V/mu m defined for the current density of 1 mu A/cm(2)) and linear Fowler-Nordheim nature (FN). However, for the understanding of the nature of the FN plot, field emission behavior of a single SnO2 nanowire is investigated. The FN plot is observed to be nonlinear in nature. A simple model explaining the field emission mechanism from the semiconducting single SnO2 nanowire is proposed. (C) 2017 American Vacuum Society.